Analysis of metagenome-assembled viral genomes from the human gut reveals diverse putative CrAss-like phages with unique genomic features - Natalya Yutin (Nature Portfolio, 2021)
Here, the authors analyze 4907 Circular Metagenome Assembled Genomes from human microbiomes and identify and characterize nearly 600 diverse genomes of crAss-like phages, finding two putative families with unusual genomic features, including high density of self-splicing introns and inteins.